BIG DATA ON DIGITAL LOGISTICS IN SUPPLY CHAIN RISK PERSPECTIVE - Resista Vikaliana (Institut Ilmu Sosial dan Manajemen Stiami, 2018)
In Industry 4.0, digital transformation moves quickly, flexibly and efficiently. Logistics and supply chains have transformed into web-based. Internet of things (IoT) and Big Data are important in the decision making process. The importance of big data doesn’t revolve around how much data you have, but what you do with it. In addition to the opportunities to use big data, there are possible risks that must be anticipated. The wide range of data that can be obtained, so that in practice key risk indicators will act as an early warning system for the entity. Key risk indicators and their parameters.